Roll motion control of a dissymmetrical wingspan aircraft - Tavares, Filipe Miguel Tanqueiro . (2015)
Submitted by Joana Lopes Dias (jdias@ubi.pt) on 2015-06-26T16:21:36Z No. of bitstreams: 1 Roll Motion Control of a Dissymmetrical Wingspan Aircraft.pdf: 12720322 bytes, checksum: 3846d08407e188c5c4c39594ece85654 (MD5)